Multidisciplinary, simulation-based training to improve review of seclusion. Issue 3 (22nd March 2021) - Akroyd, Mike; Allison, Janet; Booth, Sarah; Gilligan, Carole; Harrison, David; Holden, Victoria; Mace, Rebecca
Abstract : Purpose: Seclusion is the supervised containment of a patient, away from others, when immediately necessary to manage safety on a psychiatric inpatient ward. When seclusion is necessary, it should be used for the shortest time possible, with a regular multidisciplinary review of the patient's mental and physical health, medication and risk guiding decisions around continuation or ending of this restrictive measure. However, many medical and nursing staff can be anxious about taking part in such reviews. Simulation has been used in many areas of medicine to help people to develop competence and confidence, in a safe setting where their own needs can be paramount. This paper aims to describe the use of a blended learning approach, including simulation, to build confidence and competence amongst healthcare professionals in the safe review of seclusion. Design/methodology/approach: A multidisciplinary group, including input from individuals with lived experience of use of seclusion, put together a one-day training course, which included group debate exploring the relationship between seclusion and the Human Rights Act, guided discussion of videos exploring some aspects of practice and a half-day of simulation where multidisciplinary teams could act as the team reviewing a patient who had been secluded. Findings: This paper found that the course's blended learning approach helped participants to feel more confident in their understanding of several aspects of seclusion, including what their team discussions should include before and after seeing a patient and in knowing when to end a period of seclusion. Originality/value: While simulation is slowly becoming a more familiar component of the undergraduate and postgraduate education offer in psychiatry, the authors are unaware of any evaluation of a dedicated simulation-based training course around reviews of seclusion.